Nursing Consideration in Rhinocerebral Mucormycosis: A Case Report - Sharma, Pariksha; Rai, Hasina (Medical Journal of Armed Police Force Nepal, 2025)
Introduction: Rhinocerebral mucormycosis is a rare but aggressive opportunistic fungal infection commonly caused by Rhizopus oryzae and Rhizopus delemar that predominantly affects immunocompromised individuals, particularly those with uncontrolled diabetes mellitus or undergoing immunosuppressive therapy. It demands urgent diagnosis and multidisciplinary management due to its rapid progression and high mortality rate. Nurses play a critical role in early recognition, timely intervention, and coordination of multidisciplinary care.Case presentation: This case report describes the clinical course of Rhinocerebral mucormycosis in a patient with diabetic ketoacidosis (DKA), further complicated by post-herpetic neuralgia and lower motor neuron (LMN) facial palsy. Nursing care included implementation of the insulin protocol for DKA management, administration and monitoring of liposomal Amphotericin B, frequent neurological assessments, early detection and reporting of secondary lesions, pain management, continuous monitoring of vital parameters, infection prevention measures, and accurate documentation and communication with the healthcare team.Despite comprehensive nursing and medical management, the patient developed secondary lesions suggesting disseminated infection, central nervous system involvement, and vascular compromise hindered the possibility of surgical debridement, ultimately resulting in respiratory failure and death.Conclusions: The case highlights the crucial role of nurses in managing complex intensive care unit presentations, from early recognition of signs and symptoms, vigilant nursing assessment, prompt intervention, and interprofessional communication. Nurses are central to detecting early signs of deterioration and ensuring coordinated, evidence-based care.